High species diversity and biochar can mitigate drought effects in arid environments - Hamada E. Ali; Ahmed M. Al-Wahaibi (Frontiers in Plant Science)
IntroductionClimate change, including drought, threatens ecosystems across the globe. The current study investigated the effects of species diversity and biochar application on the performance and productivity of five native Omani species under control and drought conditions.MethodsA fully controlled greenhouse experiment was conducted in which five native species of three different diversities (one, two, and four species) were grown under four different treatments: biochar+drought, biochar, drought, and control. Productivity was measured through total biomass and root-to-shoot ratio), while performance was assessed in the form of plant functional traits (plant height, specific leaf area (SLA), and specific root length (SRL). Nutrient availability in the soil was measured using soil organic carbon (SOC) and soil total nitrogen (STN). Soil microbial content was determined using soil microbial biomass “Cmic” and soil microbial basal respiration. Biodiversity effects were analyzed using the complementarity effect (CE), selection effect (SE), and net biodiversity effect (NBE).Results and discussionThe study indicated that high diversity and biochar resulted in: 1. species with 66.6% greater total biomass and a 3% reduction in RSR, 2. enhanced species performance, with plants growing 25% taller, 50% higher SLA, and 25% higher SRL, 3. more fertile soil, with SOC and STN increasing by 40% and 33.3%, respectively, and 4. improved microbial content, with Cmic rising by 15% and basal respiration increasing by one-third under drought conditions compared to monoculture. These results highlight the intricate interactions between climate change and biodiversity, which are crucial for predicting the impact of changes in functional composition on ecosystem processes and, subsequently, for restoring arid ecosystems in Oman.